Remineralization Efficacy of an Amelogenin-Based Synthetic Peptide on Carious Lesions - Chu, Jinpu; Feng, Xiaofang; Guo, Huijing; Zhang, Tieting; Zhao, Hualei; Zhang, Qun (Frontiers in Physiology, 2018)
Objective: The aim of this study was to evaluate the remineralization efficacy of an amelogenin-based peptide on initial enamel carious lesions in vitro. Furthermore, we attempted to provide insights into the possible mechanism of the remineralization, including determining the calcium-binding properties of the peptide and its effects on calcium phosphate mineralization. Methods: The peptide comprising the N-terminus and the C-terminus of porcine amelogenin was synthesized by Synpeptide Co Ltd . Fifty specimens were randomly assigned to five immersing treatment groups for 12 days: remineralizing medium only; 12.5 μg/mL peptide + remineralizing medium; 25 μg/mL peptide + remineralizing medium; 50μg/mL peptide + remineralizing medium; fluoride + remineralizing medium. After immersion, mean mineral loss before and after remineralization of each specimen was determined using micro-CT. Mean mineral gain after remineralization was calculated. Calcium binding properties were measured by ITC. TEM and FT-IR were used to determine the effects of the peptide on calcium phosphate mineralization. Results: A significant decrease in mineral loss after remineralization process in all groups was observed (p<0.05). Treatment in remineralizing medium resulted in the lowest mineral gain while the fluoridated treatment exhibited the highest mineral gain among all groups. Inclusion of synthetic peptide in the remineralizing medium exhibited a higher mineral gain and the gain of 50μg/mL group was greater than that of the 25μg/mL group. No significant difference in mineral gain was observed between the remineralizing medium only group and the 12.5μg/mL peptide group (p>0.05). ITC values showed that the Ca2+-binding affinity of the peptide is about 9.914×104M-1. Furthermore, the peptide was found to inhibit calcium phosphate precipitation and stabilize ACP formation for more than 2h and finally transform into ordered hydroxyapatite crystals. Conclusions: Specific concentrations of the amelogenin-based synthetic peptide promoted in vitro remineralization, with higher concentrations exhibiting significantly greater remineralization. This study presented evidence suggesting that the peptide may act as a Ca2+carrier as well as a regulating factor. When the stabilizing calcium and phosphorus ions bind with the peptide they become biologically available for the remineralization of deeper carious lesions, while also regulated by the peptide to transform into ordered hydroxyapatite crystals.